Prevalence and associated factors of symptoms of pica among adolescent schoolchildren in northern Sudan: a cross-sectional study - Mohamed A. Ahmed; Abdullah Al-Nafeesah; Ashwaq AlEed; Ishag Adam (Journal of Eating Disorders, 2023)
Plain English summary We conducted this study from July to September 2022 to estimate the rate of adolescents who would eat non-food items (pica) in Sudan. We gathered sociodemographic characteristics through a questionnaire. Of the 384 enrolled adolescents, 180 (46.9%) were male and 204 (53.1%) were female. We found that 118 (30.7%) adolescents would eat non-food items (pica) and that the most common type was eating clay and sand (102 adolescents, 86.4%), followed by eating ice (14 adolescents, 11.8%) and flour (starch; 2 adolescents, 1.6%). Females and those with a lower level of father’s education were likely to eat non-food items.